A Peep into the Jungle of Literature on Informal Credit Arrangement : With Focus on Market Interlinkages - Acharya, Keshav P. (NRB Economic Review, 2000)
The mainstream economic theory completely ignored the analysis of microeconomic arrangement in the traditional societies of low income countries. There has been a change in attitude of economists beginning from the 1970s. One of the aspect that has generated the interest of academic economist in the last three decades or so is the informal credit arrangement. This essay reviews the theoretical dimension of debate in informal credit that surface during the 1970s and 1980s. This short essay captures the major tenets of the debate.The paper begins with a brief introduction of the subject matter. The whole controversy is then divided into the main stream and the alternative approaches. Both of these approaches are analysed in terms of: (i) credit-land, (ii) credit-labour, and (iii) credit output interlinkages. The paper ends with a very short description of the treatment of interlinked credit in Nepal.